THE PRODUCTION OF FREEZE-DRIED EGG YOLK POWDER AND ITS EFFECT ON THE QUALITY OF GARUT RAM LIQUID SEMEN - Ariantie, Oriza Savitri; Amrozi, Amrozi; Yusuf, Tuty Laswardi; Rochman, Nurul Taufiqu; Purwantara, Bambang (Universitas Syiah Kuala, 2021)
This research aims to evaluate the protective potency of freeze-dried egg yolk powder on Garut ram sperm during the liquid semen preservation process. Semen with good sperm quality was divided into three groups and diluted using the following Tris diluents: fresh egg yolk-Tris (FEY-Tris), commercial egg yolk powder-Tris (CEY-Tris), and freeze-dried egg yolk powder-Tris (DEY-Tris). Semen that had been diluted was observed every 12 hours until sperm progressive motility was 50%. Sperm quality was tested for progressive motility percentages, viability, intact plasma membrane (IPM), and intact acrosome (IA). Fresh egg yolk had a particle size of 14460.00330.76 nm, with polydispersity index value (PI) and zeta potential (ZP) being 1.000.11 and -9.220.30 mV, respectively. The particle size of commercial egg yolk powder was 877.90168.86 nm with PI value 0.340.04 and ZP-28.71.24 mV. The particle size of freeze-dried egg yolk powder was 1296.0086.73 nm, with PI value 0.700.04 and ZP-34.50.64 mV. Progressive motility percentage showed that DEY-Tris diluent managed to survive to 51.116.06% for 168 hours, compared to FEY-Tris (51.256.74%) which survived for 156 hours, although no longer than CEY-Tris diluent (53.476.33%) which survive for 180 hours (P0.05). Higher sperm motility was also supported by viability percentage, IPM, and IA, which were all higher (P0.05). In conclusion, freeze dried egg yolk powder mixed with Tris buffer was able to maintain sperm quality during the liquid semen preservation process.